Front Cover: Pyrene‐Thiol‐modified Pd Nanoparticles on Carbon Support: Kinetic Control by Steric Hinderance and Improved Stability by the Catalyst‐Support Interaction (ChemCatChem 23/2020). Issue 23 (9th November 2020) - Yoshii, Takeharu; Umemoto, Daiki; Yamamoto, Masanori; Kuwahara, Yasutaka; Nishihara, Hirotomo; Mori, Kohsuke; Kyotani, Takashi; Yamashita, Hiromi
Abstract : The Front Cover shows Pd nanoparticle catalysts modified with pyrene‐thiol ligands on carbon supports for aerobic oxidative dehydrogenation of amines to imines. In their Communication, T. Yoshii et al. experimentally and theoretically demonstrate that the rate‐limiting imine product desorption is boosted as a result of the steric hindrance of the ligands, and the catalytic stability is significantly improved by the π−π interactions between catalyst and support, which make this material an active and stable catalyst for the amine dehydrogenation reaction. This study provides a design guideline to unlock hidden catalytic properties of metal nanoparticles through surface modification. More information can be found in the Communication by T. Yoshii et al.